2014
DOI: 10.1186/1471-2407-14-255
|View full text |Cite
|
Sign up to set email alerts
|

Space-time clusters of breast cancer using residential histories: A Danish case–control study

Abstract: BackgroundA large proportion of breast cancer cases are thought related to environmental factors. Identification of specific geographical areas with high risk (clusters) may give clues to potential environmental risk factors. The aim of this study was to investigate whether clusters of breast cancer existed in space and time in Denmark, using 33 years of residential histories.MethodsWe conducted a population-based case–control study of 3138 female cases from the Danish Cancer Registry, diagnosed with breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A good example is the method of Q-statistics, developed by Jacquez and others (Jacquez et al 2006), that searches for clusters of disease cases compared to controls in space and time based on residential history data. Recent studies have used Q-statistics in identifying space-time clusters of breast cancer in Denmark (Nordsberg et al 2014), for example. These trajectory-based methods offer great possibilities for health research, but their application requires detailed data on people's migration trajectories that is not widely available in countries like the United States.…”
Section: Space-time Cluster Detection Methodsmentioning
confidence: 99%
“…A good example is the method of Q-statistics, developed by Jacquez and others (Jacquez et al 2006), that searches for clusters of disease cases compared to controls in space and time based on residential history data. Recent studies have used Q-statistics in identifying space-time clusters of breast cancer in Denmark (Nordsberg et al 2014), for example. These trajectory-based methods offer great possibilities for health research, but their application requires detailed data on people's migration trajectories that is not widely available in countries like the United States.…”
Section: Space-time Cluster Detection Methodsmentioning
confidence: 99%
“…As an example, Nordsborg et al . [NME*14] provide a visual analysis of breast cancer data from the Danish cancer registry. In a similar way, Nordsborg et al .…”
Section: Visual Analytics For Epidemiological Researchmentioning
confidence: 99%
“…Residential histories have been used for geospatial modeling to estimate arsenic water source histories [23], arsenic concentrations in private well water based on the nearest neighbor [24], and satellite imagery as a proxy for farmland [25]. They have also been used to examine space time clusters of cancer [26][27][28][29]. Several CM studies have shown an association with early migration (childhood) to sunny places [30][31][32][33], but findings among studies using lifetime measures of UVR have been inconsistent due to varying exposure assessment methods for sun exposure or UVR [20,[34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%